Paediatric haematologists' attitudes regarding haematopoietic cell transplantation as treatment for sickle cell disease. (12th November 2019) - Stallings, Alicia M.; Majhail, Navneet S.; Nowacki, Amy S.; Onimoe, Grace I.; Hanna, Rabi; Piccone, Connie M.
Summary: Beginning early in childhood, patients with sickle cell disease [SCD; a group of genetic haemoglobin disorders characterized by the sickle or HbS mutation ( HBB E7V)] are at risk of life‐threatening and debilitating health events. Despite the high morbidity and mortality of this disease, haematopoietic cell transplantation (HCT), a curative therapy for SCD, remains underutilized. A variety of factors, including the limited availability of suitable donors, play a role in this trend, but do not fully explain the low frequency with which this therapy is employed. The objective of this study was to identify paediatric haematologists' attitudes about HCT as a treatment option for SCD, and to describe the impact of these attitudes on their practices of discussing HCT with families of children affected by this disease. A nationwide survey of paediatric haematologists in the United States was conducted between February and May 2016. Two hundred and eighty‐seven surveys were included in the final analysis (response rate 20%). On average, respondents reported informing 42% of families about HCT as a treatment option ( N  = 248, 95% confidence interval: 38–46). Clinician attitudes about the cost and safety of HCT were associated with practices of discussing this therapy with families. These findings suggest that clinician attitudes and referral practices may play a role in the underutilization of this therapy in the SCD population.